Nusantara Digital Museum Based on Virtual Tour and Virtual Guide: A Case Study of Woven Fabric, Shawls, Songket and Ulos - Lubis, Januardi Rosyidi; Rahayu, Perra Budiarti; Irawan, Feri; Siregar, Selamat Riadi (SAINTIS Publishing, 2024)
This study aims to digitize ulos, woven, songket and shawl fabrics spread across several districts and cities into a digital museum based on virtual tours and virtual guides. Digitization contains images of fabrics, then the patterns, symbols and motifs contained in each fabric will be explained as a learning of noble values, philosophy and history in each fabric as a cultural heritage based on local wisdom. The noble values, philosophy and historical meaning of the fabric are explained through the Indonesian digital museum platform as a form of love for museums with a cultural approach that contains meaning and significance. The Indonesian digital museum contains woven fabrics, songket, shawls and ulos used by the community, but few of them know the meaning, patterns and motifs contained in them. The focus of this research is a form of love for museums that are now starting to be abandoned. Departing from technological developments, a website-based Indonesian digital museum platform was designed and built that can be visited by the public online with a virtual tour experience and at the same time a guide (virtual guide). The method used in designing and building this Indonesian digital museum is the SDLC (Software Development Life Cycle) method. The research stages begin with system requirements analysis, then interactive museum design and supported by program code implementation so that during testing and verification it is ready for use.